2019
DOI: 10.35631/ijemp.28001
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Mergers and Acquisitions on Financial Performance of Listed Companies in China

Abstract: The purpose of this paper is tantamount to study whether mergers and acquisitions (M&A) improve the financial performance of Chinese listed companies. We use panel data regression to examine 434 completed M&A activities from 2012 to 2016 initiated by Chinese companies listed on the Shanghai and Shenzhen Stock Exchanges. The evidence indicates that, on average, the firm performed better after the M&A activities. We further divide all sample enterprises into three different types of M&A. The resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 0 publications
1
8
0
1
Order By: Relevance
“…Our evidence supports the view that M&A can improve the operating performance of companies. In the domestic Russian M&A market, the operating profit margin of companies improves after horizontal deals between large companies, in line with previous research of other M&A markets ( [15], [16], [17], [21]). However, in Russia, unlike many other countries (see [13]), real GDP growth does not impact the size of the national M&A market in value terms or the operating profit margin of companies after deals.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our evidence supports the view that M&A can improve the operating performance of companies. In the domestic Russian M&A market, the operating profit margin of companies improves after horizontal deals between large companies, in line with previous research of other M&A markets ( [15], [16], [17], [21]). However, in Russia, unlike many other countries (see [13]), real GDP growth does not impact the size of the national M&A market in value terms or the operating profit margin of companies after deals.…”
Section: Discussionsupporting
confidence: 89%
“…Studies show that horizontal deals are more likely to increase operating profit margin. The research at [15], on a sample of 90 French listed companies M&A, and [16] on a sample of 434 Chinese M&A, both concluded that horizontal M&A lead to a cost reduction via economies of scale.…”
Section: Literature Reviewmentioning
confidence: 99%
“…On the other hand, a positive link between M&A and financial performance post-merger has also been discovered (e.g. Herwadkar et al, 2022;Chen et al, 2019) and it is linked to other measures of the financial performance of a merged company. Aggarwal and Garg (2019) observed a significant positive impact on the profitability and liquidity position of acquires five years after the merger.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…Penelitian sebelumnya oleh (Ombaka dan Jagongo, 2018) dan (Chen et al, 2019) menuturkan bahwa terdapat perbedaan signikan terhadap rasio profitabilitas dengan proksi return on assets pada perusahaan yang melakukan akuisisi. Sebaliknya penelitian oleh (Hachem dan Sujud, 2018) dan (Firdaus & Dara, 2020) menyatakan tidak terdapat perbedaan signifikan.…”
Section: Gambar 3 Survei Kpmg Merger Dan Akuisisiunclassified